2015
DOI: 10.4314/jfas.v4i2.5
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and antioxidant activity of <i>Apis mellifera</i> bee pollen from northwest Algeria

Abstract: The aim of this study was to assess the nutritional composition and antioxidant activity of bee pollen produced in the North western region of Algeria. The content of total phenolic compounds, flavonoids, and antioxidant activity using the molybdate ion reduction method were determined. The mean contents of phenolic compounds and total flavonoids were 30.46 ± 8.22 mg of GAE.g -1 pollen and 8.92 ± 5.5 mg of RE.g -1 pollen, respectively. High antioxidant activities were found for the molybdate ion reduction meth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
17
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 13 publications
(15 reference statements)
5
17
0
1
Order By: Relevance
“…The in vitro antioxidant capacity of Greek bee pollen was affected by the ethanolic extract concentration. The mother bee pollen ethanolic solution (125,000 mg L −1 ) recorded the higher antioxidant capacity (88.26%) followed by those of 30,000 (86.81%), 25,000 (81.75%), 10,000 (71.06%), and 5000 (68.7%) mg•L −1 , respectively (Table 2) Present results are in agreement with previous studies involving American [23], Greek [14], and Algerian [24] bee pollen samples, where the high antioxidant capacity of the respective methanolic extracts was highlighted. It should be stressed that the antioxidant capacity of bee pollen ethanolic extract is strictly related to its phenolic fraction, as it has been well demonstrated in the literature [25].…”
Section: In Vitro Antioxidant Capacity Of Bee Pollen Ethanolic Extractssupporting
confidence: 92%
See 1 more Smart Citation
“…The in vitro antioxidant capacity of Greek bee pollen was affected by the ethanolic extract concentration. The mother bee pollen ethanolic solution (125,000 mg L −1 ) recorded the higher antioxidant capacity (88.26%) followed by those of 30,000 (86.81%), 25,000 (81.75%), 10,000 (71.06%), and 5000 (68.7%) mg•L −1 , respectively (Table 2) Present results are in agreement with previous studies involving American [23], Greek [14], and Algerian [24] bee pollen samples, where the high antioxidant capacity of the respective methanolic extracts was highlighted. It should be stressed that the antioxidant capacity of bee pollen ethanolic extract is strictly related to its phenolic fraction, as it has been well demonstrated in the literature [25].…”
Section: In Vitro Antioxidant Capacity Of Bee Pollen Ethanolic Extractssupporting
confidence: 92%
“…In a previous study, total phenolic content of Greek bee pollen methanolic extracts was found higher, ranging between 10.49 ± 0.3 mg of protocatechuic acid equivalents per gram of pollen [14]. The same holds for TPC content values (15.91 ± 0.05-34.85 ± 0.08 mg GAE/g) of different American bee pollen types [23] or Algerian ones (30.46 ± 8.22 mg GAE/g) [24]. However, the observed differences may be also attributed to harvesting year, practices of bee pollen collection and processing, the solvent used for the extraction of polyphenols, along with the plant taxa contribution.…”
Section: Total Phenolic Content Of Bee Pollen Ethanolic Extractsmentioning
confidence: 56%
“…Volume 10, Number 1, January 2020 In this study, the antioxidant activities of bee pollen extracts are associated with the content of phenolic compounds which is similar to the previous reports [19], [20], [21]. On the other hands, this does not appear to be true for other biological activities [22], [23].…”
supporting
confidence: 89%
“…However, [8,16,17,21] observed smaller values in pollen from Portugal, Lithuania, Brazil and Algeria, respectively.…”
Section: Discussionmentioning
confidence: 99%